LITAF, a BCL6 target gene, regulates autophagy in mature B‐cell lymphomas. (25th June 2013) - Bertolo, Cristina; Roa, Sergio; Sagardoy, Ainara; Mena‐Varas, Maria; Robles, Eloy F.; Martinez‐Ferrandis, Jose I.; Sagaert, Xavier; Tousseyn, Thomas; Orta, Alberto; Lossos, Izidore S.; Amar, Salomon; Natkunam, Yasodha; et al.
Summary We have previously reported that LITAF is silenced by promoter hypermethylation in germinal centre‐derived B‐cell lymphomas, but beyond these data the regulation and function of lipopolysaccharide‐induced tumour necrosis factor (TNF) factor (LITAF) in B cells are unknown. Gene expression and immunohistochemical studies revealed that LITAF and BCL6 show opposite expression in tonsil B‐cell subpopulations and B‐cell lymphomas, suggesting that BCL6 may regulate LITAF expression. Accordingly, BCL6 silencing increased LITAF expression, and chromatin immunoprecipitation and luciferase reporter assays demonstrated a direct transcriptional repression of LITAF by BCL6. Gain‐ and loss‐of‐function experiments in different B‐cell lymphoma cell lines revealed that, in contrast to its function in monocytes, LITAF does not induce lipopolysaccharide‐mediated TNF secretion in B cells. However, gene expression microarrays defined a LITAF‐related transcriptional signature containing genes regulating autophagy, including MAP1LC3B (LC3B). In addition, immunofluorescence analysis co‐localized LITAF with autophagosomes, further suggesting a possible role in autophagy modulation. Accordingly, ectopic LITAF expression in B‐cell lymphoma cells enhanced autophagy responses to starvation, which were impaired upon LITAF silencing. Our results indicate that the BCL6‐mediated transcriptional repression of LITAF may inhibit autophagy in B cells during the germinal centre reaction, and suggest that the constitutive repression of autophagy responses in BCL6‐driven lymphomas may contribute to lymphomagenesis.